Intellischool: A Student Information System for Senior High School - Campanan, Azelle Marie; Bermejo, Ruby Mae; Madrigal, Dennis (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
An IntelliSchool: A Student Information System (SIS) for Senior High School (SHS) is a software application intended to oversee and simplify different aspects of student-related academic information efficiently. This study aimed to ensure data accuracy and consistency, develop a paperless and web-based class record, ensure fairness and transparency in generating forms, and enhance parent-school communication and involvement by incorporating a messaging system. Descriptive-developmental approach was employed in this study. Interviews and direct observation of transaction processes were used as data collection methods in developmental approach. The software development life cycle (SDLC) adopted was Rapid Application Development (RAD), encompassing stages from requirements planning, user design, development, and system launch. The system was developed using Code Igniter PHP Framework, MySql, JQuery, and Code Espresso SMS Gateway technologies. In descriptive approach, test case to check systems functionality and Post Study System Usability Questionnaire (PSSUQ) were administered sequentially to 5 IT experts and 35 end-users. In data analysis, standard mean was employed. The test case obtained "passed" rating. In PSSUQ, overall mean is 1.21 across system usefulness, interface quality, and information quality. The system has undergone pilot implementation through locally hosted network infrastructure, fulfilling its intended nature and purpose. The recommendation was to use a server that accommodates users without sacrificing the system’s performance.